2021
DOI: 10.3389/fpls.2021.680545
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Blue and Red LEDs Increase the Morphophysiological Performance and Furanocoumarin Production of Brosimum gaudichaudii Trécul in vitro

Abstract: Brosimum gaudichaudii is a plant species with medicinal relevance due to its furanocoumarin accumulation. The accumulation of these compounds in the root promotes predatory extractivism, which threatens the conservation of the species. In addition, little is known about the conditions for culturing of this species in vitro. The present study aimed to investigate how the application of different spectra of LEDs (white, blue, red, and combinations of blue and red at 1:1 and 3:1 ratios) can impact the morphophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Unlike GR or BGR, higher fluorescence intensity in BR suggests higher absorption of red light by chlorophyll a and b, promoting the excitation of electrons in PSI and PSII, leading to a distinct OJIP curve shape with rapid transitions between the O, J, I, and P steps. Rapid transitions induced in the OJIP curves due to red light are consistent with studies in other species ( Costa et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Unlike GR or BGR, higher fluorescence intensity in BR suggests higher absorption of red light by chlorophyll a and b, promoting the excitation of electrons in PSI and PSII, leading to a distinct OJIP curve shape with rapid transitions between the O, J, I, and P steps. Rapid transitions induced in the OJIP curves due to red light are consistent with studies in other species ( Costa et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Frszczak et al 27 reported that the average height of Anethum graveolens was proportional to the amount of red light after 28 days of culture, that value was highest in the treatment using a combination of 70% red LED and 10% blue LED. Several other studies have also shown that red LED increased the height of various plantlet species such as Rehmannia glutinosa 13 , grape 28 and Brosimum gaudichaudii 29 .…”
Section: Discussionmentioning
confidence: 78%
“…Several authors have also indicated that the use of mixed LED lights (blue and red), in the right proportions, may affect the increase of biomasses and the production of secondary metabolites. Costa et al [ 67 ] used blue and red lights in a 3:1 proportion, respectively, to increase the biomass and bergapten production of Brosimum gaudichaudii seedlings. Conversely, the combination of blue and red lights, in a ratio of 2:1, was optimal for L .…”
Section: Resultsmentioning
confidence: 99%